Penduduk Usia Lanjut Di Propinsi Daerah Istimewa Yogyakarta: Studi Kualitatif Terhadap Permasalahan Usia Lanjut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT In Indonesia, it is tradition that children should have take'cre of their elderly parents. information global transformation and industry with positive traditional value may be difficult if faced with aging problem in developing countries. Although in small numbers, developing of home for elderly can refer to this trend. The objective of this study is to find out the physical, psychological and economic-social problem of the elderly in Yogyakarta special province. One hundred elderly people from rural (Bantu' District) and urban (Yogyakarta municipality) area were chosen purposively on this study. In-depth interview and focus group discussion (FGD) were used for collecting data. There were three FGDs, family group, key person group and program organizer group. Qualitative analysis was used for data analyzing. Results showed that elderly people were identified as people who have been physical and psychological declining. Elderly people had a lot of problem, such as decreasing productivity, keeping their status and mobility declining.